The absorbing haloes around high-redshift radio galaxies: the UVES view - Wilman, R; Jarvis, M; Rottgering, H; Binette, L (2003)
We summarise the properties of the absorbing haloes around two high-redshift radio galaxies studied with the VLT-UVES echelle spectrograph. The absorbers in 0943 - 242 (z = 2.92) exhibit little further structure compared with previous data-the main absorber still has N(HI) similar or equal to 10(19) cm(-2)-reinforcing the picture in which the absorbing gas occupies a smooth shell beyond the emission line halo. In 0200+015 (z = 2.23) the main absorber now splits into two spatially-resolved systems with N(HI) = 4 x 10(14) cm(-2), one of which has strong CIV absorption, implying a metallicity of Z similar or equal to 10 Zcircle dot. We explain the differences between the two sources with an evolutionary scenario, invoking interaction with the expanding radio source and metal enrichment via a starburst superwind. (C) 2003 Elsevier B.V. All rights reserved.